Analisis Kualitas Udara Berdasarkan Volume Lalu Lintas di Jalan Kedung Cowek Surabaya - Andreas Leonardo Ginting; Mohammad Mirwan (Yayasan Literasi Sains Indonesia, 2022)
The increasing number of people in the world has caused the air to be increasingly polluted. In everyday time of day the exhaust gases from transportation are mostly inhaled from the combustion output using fuel whichhas relatively high levels. Carbon monoxide has a negative influence on the body because CO is able to bind through blood cells or hemoglobin which transports oxygen to all the body and interferes with the distribution of oxygen to the blood. This study aims to find out the average picture of the level of CO concentration and the influence of the number of motorized vehicles on the level of CO concentration on Jalan Kedung Cowek Surabaya.In this study, the CO measurement used aeroaqual tools. The results of research conducted for 1 week on Tuesday (representing weekdays), Saturdays (representing half-working days) and Sundays (representing holidays) showed differences in CO concentration and vehicle volume at each time”. In the morning and evening, the average CO concentration tends to be higher than during the day. From the results of the Multivariate Anova analysis, it can be concluded that the existing time difference greatly affects the concentration of CO and the volume of the vehicle produced. In addition, CO concentration is also influenced by meteorological factors such as temperature, direction and wind speed.